In-vitro scolicidal activity of Mallotus philippinensis (Lam.) Muell Arg. fruit glandular hair extract against hydatid cyst Echinococcus granulosus - Gangwar, Mayank; Verma, Vijay C; Singh, Tryambak D; Singh, Sushil K; Goel, RK; Nath, Gopal (Asian Pacific journal of tropical medicine, 2013)
Objective: To investigate new scolicidal agent from natural resources to cope with the side effects associated with synthetic drugs in Echinococcosis. Methods: The scolicidal potential of methanolic fruit powder extract (10 and 20 mg/mL) of Mallotus philippinensis ( M. philippinensis ) was investigated. Viability of protoscoleces was confirmed by trypan blue exclusion method, where mortality was observed at concentration of 10 and 20 mg/mL in 60 min treatment against Echinococcus granulosus ( E. granulosus ), under in-vitro conditions with reference to the known standard drug Praziquantel . Results: At concentration 10 and 20 mg/mL, the mortality rate was observed 97% and 99% respectively for 60 min treatment; while up to 93% mortality was observed with 20 mg/mL for only 10 min treatment. The concentration above 20 mg/mL for above 2 h showed 100% mortality, irrespective of further incubation. Conclusions: As compared with the standard anti-parasitic drug Praziquantel our extract has significant scolicidal activity with almost no associated side effects.